2009
DOI: 10.1007/s00011-009-8057-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of retinoid against endotoxin-induced mastitis in rats

Abstract: These results suggest that retinoid protected against LPS-induced mastitis in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Histologic evaluation is in agreement with these results. These results are consistent with our previous findings [13,49], indicating that correlation between these two enzymes exists. In response to chemotactic stimuli generated by invading pathogens, PMN migrates (diapedesis) from blood into milk [50].…”
Section: Discussionsupporting
confidence: 94%
“…Histologic evaluation is in agreement with these results. These results are consistent with our previous findings [13,49], indicating that correlation between these two enzymes exists. In response to chemotactic stimuli generated by invading pathogens, PMN migrates (diapedesis) from blood into milk [50].…”
Section: Discussionsupporting
confidence: 94%
“…So, LPS-induced inflammatory models are recognized as valuable tools with which to study the effects of mastitis [23,24]. Experiments with LPS-induced mastitis in rats suggest that large scale production of inflammatory cytokines, such as TNF-α, IL-1β, IL-8, might contribute to tissue damage [15,16,25]. Therefore, we hypothesized that suppressing the production of inflammatory mediators by leukocytes, endothelial and epithelial cells could prevent mammary tissue damage during the development of mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that an uncontrolled inflammatory response, including the over production of inflammatory mediators, such as TNF-α, IL-1β, is the main pathogenesis involved in mastitis [15,16,25]. Among the inflammatory mediators induced by TLR4/NF-κB, IL-1β has been reported to have specific chemo-attractant and activation effects on phagocytic cells, as well as on other cell types [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the administration of retinoid acids protects rats against neutrophil-induced oxidative stress in acute experimental mastitis (Gu et al, 2009a;2009b). A mechanism by which this protection is conferred is through TLR4.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%